CUSTOMER SATISFACTION: IN SERVICE QUALITY RELATIONSHIP TO CUSTOMER LOYALTY - Hanik Mawaddah; M Trihudiyatmanto (Journal of Social Sustainability Management, 2021)
This study aims to analyze the effect of Service Quality on Customer Loyalty with Customer Satisfaction as a mediating variable. The population and sample of this study were users of J&T Express delivery services in Mojotengah Wonosobo District. Samples were conducted using non-probability sampling method. Data collection was carried out by using questionnaires distributed directly to the community using J&T Express Wonosobo Branch who had shipped goods using J&T Express delivery service as many as 100 questionnaires. The statistical method uses Structural Equation Modeling (SEM) analysis. The results of this study indicate that Service Quality has a positive effect on customer loyalty, Service Quality has a positive effect on Customer Satisfaction, Customer Satisfaction has a positive effect on Customer Loyalty, Service Quality has a positive effect on Customer Loyalty with Customer Satisfaction as a mediating variable in J&T Express delivery services. Penelitian ini bertujuan untuk menganalisis pengaruh Service Quality (kualitas pelayanan) terhadap Customer Loyalty (loyalitas pelanggan) dengan Customer Satisfaction (kepuasan pelanggan) sebagai variabel mediasi. Populasi dan Sampel dari penelitian ini adalah pengguna jasa pengiriman J&T Express di Kecamatan Mojotengah Wonosobo. Sampel yang dilakukan dengan metode non probability sampling pengumpulan data dilakukan dengan kuesioner disebar langsung pada masyararakat pengguna J&T Express Cabang Wonosobo yang pernah melakukan pengiriman barang yang menggunakan jasa pengiriman J&T Express sebanyak 100 kuesioner. Metode statistik menggunakan analisis Structural Equation Modeling (SEM). Hasil penelitian ini menunjukkan bahwa Service Quality berpengaruh positif terhadap customer loyalty, Service Quality berpengaruh positif terhadap Customer Satisfaction, Customer Satisfaction berpengaruh positif terhadap Customer Loyalty, Service Quality berpengaruh positif terhadap Customer Loyalty dengan Customer Satisfaction sebagai variabel mediasi pada jasa pengiriman J&T Express.